2019
DOI: 10.3847/2041-8213/ab14e5
|View full text |Cite
|
Sign up to set email alerts
|

Confirming Interstellar C60 + Using the Hubble Space Telescope

Abstract: Recent advances in laboratory spectroscopy lead to the claim of ionized Buckminsterfullerene (C + 60 ) as the carrier of two diffuse interstellar bands (DIBs) in the near-infrared. However, irrefutable identification of interstellar C + 60 requires a match between the wavelengths and the expected strengths of all absorption features detectable in the laboratory and in space. Here we present Hubble Space Telescope (HST) spectra of the region covering the C + 60 9348, 9365, 9428 and 9577 Å absorption bands towar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 33 publications
(57 reference statements)
5
78
0
2
Order By: Relevance
“…For tetracene, the fragmentation pattern exhibits the typical bi-modal structure as in the case of triphenylene. [29][30][31] and very recently in diffuse ISM with a robust confirmation from the Hubble telescope [32]. A key difference between fullerenes and the PAHs discussed above is the presence of 5-membered rings in fullerenes.…”
Section: Pyrene (C 16 H +mentioning
confidence: 79%
“…For tetracene, the fragmentation pattern exhibits the typical bi-modal structure as in the case of triphenylene. [29][30][31] and very recently in diffuse ISM with a robust confirmation from the Hubble telescope [32]. A key difference between fullerenes and the PAHs discussed above is the presence of 5-membered rings in fullerenes.…”
Section: Pyrene (C 16 H +mentioning
confidence: 79%
“…Initially identified in a young planetary nebula, they are now seen in a wide variety of sources. Interstellar C + 60 , originally proposed by Foing & Ehrenfreund (1994), is now firmly detected at optical wavelenths (Cordiner et al 2019). In fact, there is now good observational evidence for the transformation of PAHs to fullerenes under the influence of UV radiation, a process that is also understood theoretically (Berné & Tielens 2012) and simulated experimentally (Zhen et al 2014).…”
Section: Molecular Physics: Pahs Fullerenesmentioning
confidence: 82%
“…[71] García-Hernández et al presented evidence that that fullerenes and PAHs coexist in the circumstellar ejecta of low-excitation and H-containing planetary nebula in our galaxy and in the Small Magellanic Cloud. [72] Based on Hubble Space Telescope data, combined with ground-based observations, in a 2019 report Cordiner et al [73] conclusively confirmed the presence of C 60 + in low-density, strongly-irradiated environments of interstellar space. To explain how the C 60 fullerene could form in the ISM, several "top-down" schemes have been proposed where larger carbon clusters shrink to reach C 60 .…”
Section: Proposed Routes To Fullerenes In the Ismmentioning
confidence: 93%